Hemato-biochemical profile of tambaqui (Colossoma macropomum Cuvier, 1816) comparing different growth phases in aquaponic systems - Paola Fabiana Fazzi Gomes; Helen Cristiane Araújo Souza; Marcela Cardoso Sena; Joane Natividade Souza; Marco Shizuo Owatari; Fabio Carneiro Sterzelecki; Nuno Filipe Alves Correia de Melo; Glauber David Almeida Palheta (Ciência Animal Brasileira, 2024)
The aim of this study was to evaluate the haemato-biochemical parameters of